PEMILIHAN KEPALA DESA SECARA SERENTAK DAN HUBUNGANNYA DENGAN DEMOKRASI (STUDI TERHADAP PEMILIHAN KEPALA DESA PRAIBAKUL DAN MBATAPUHU, KECAMATAN HAHARU, KABUPATEN SUMBA TIMUR TAHUN 2021) - Kaka, Imanuel; Yohanes, Saryono; Tupen, Rafael R (Petitum Law Journal, 2023)
Regional autonomy is an example of a government system chosen by the central government in order to get closer to the community in development in order to achieve the state's goals. Talking about regional autonomy, or the division of work tasks by the central government to regional governments, one of the many concrete examples can be seen from the existence of Law Number 6 of 2014 concerning Villages, as Villages are defined as legal community units that have territorial boundaries and authority. to regulate, manage the government, the interests of local communities based on community initiatives, original rights, and/or traditional rights that are recognized and respected in the government system of the unitary state of the Republic of Indonesia. This research is normative legal research, namely legal research carried out by examining library materials or secondary data. Apart from that, empirical juridical legal research methods are also carried out, namely research methods that review the function of a law or rule in terms of its application in the scope of society. The results of this research show: (1) In the context of simultaneous general elections for village heads, there are several ways in which the relationship with democracy can be explained, namely: (a) People's Empowerment: Simultaneous general elections for village heads enable the active participation of village residents in village head elections them, (b) Free and Secret Choice: In simultaneous village head elections, village residents have the freedom to choose village head candidates according to their wishes, (c) Accountability and Transparency: Simultaneous village head elections also contribute to accountability and transparency in village government, and (d) Leadership Legitimacy: Simultaneous village head elections provide legitimacy to the elected leaders. (2) The mechanism and process for selecting Village Heads and their relationship with Democracy in Praibakul and Mbatapuhu Villages with the mechanism for simultaneous village head elections which are still relatively new, simultaneous village head elections are carried out in a small number of areas, which with the existence of the Village Law can regulate matters related to the election of village heads in more detail. For example, related to the issue of village election funds, which currently in accordance with the provisions of the law come from district and city APBD funds, which is different from previously where village election funds came from the villages holding the village elections.